2013 First IEEE Working Conference on Software Visualization (VISSOFT) 2013
DOI: 10.1109/vissoft.2013.6650530
|View full text |Cite
|
Sign up to set email alerts
|

Finding structures in multi-type code couplings with node-link and matrix visualizations

Abstract: Software systems are often modeled and visualized as graphs in order to understand their higher-level structure: code entities are connected by dependencies or couplings. However, when only considering one type of code coupling such as method calls, the understanding gained stays limited to this specific aspect. Encoding multiple types of code coupling in the graph promises to broaden the understanding. Different approaches already exist for visually discerning those types in graph diagrams. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…The long-term goal of the research is to develop right methodologies to unravel the "interesting" information within email data. We aim to find "interesting" structures by integrating node-link and matrix visualizations [18]. The challenging tasks will be delivered by considering visual analytics and algorithm analysis in combination which will be highly useful in the Electronic Discovery (E-discovery) domain.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term goal of the research is to develop right methodologies to unravel the "interesting" information within email data. We aim to find "interesting" structures by integrating node-link and matrix visualizations [18]. The challenging tasks will be delivered by considering visual analytics and algorithm analysis in combination which will be highly useful in the Electronic Discovery (E-discovery) domain.…”
Section: Discussionmentioning
confidence: 99%
“…TreeMatrix [18] combines node-link and matrices to depict high level and low level structures of source code, along with their relationships. Abuthawabeh et al (2013) [19] found that both matrix and parallel node-link visualizations were similarly performant in showing multiple types of couplings. Although these approaches are useful to show the structure of the design at some points in time, they do not focus on representing how the design evolves over time.…”
Section: B Software Visualizationmentioning
confidence: 98%
“…This variation of the DSM is also called domain mapping matrix (DMM) and is based on the same modelling notation as the DSM. The DSM layout requires product elements to be listed strictly on the horizontal and vertical axes, making it a rather rigid but at the same time very compact and scalable way of describing structures of single products (Abuthawabeh et al, 2013). This well-defined arrangement has proved to be particular useful for computational analysis methods.…”
Section: Adjacency Matricesmentioning
confidence: 99%